FISCAL AND REGULATORY ROLE OF INDIRECT TAXES IN UKRAINE - SLAVKOVA, Alla (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article analyzes the fiscal and regulatory role of indirect taxes in Ukraine. The advantages and disadvantages of indirect taxes in Ukraine are identified. The revenues from indirect taxes in the structure of the consolidated budget of Ukraine for 2017-2022 are analyzed. The directions for increasing the level of fiscal efficiency of indirect taxes are highlighted. The regulatory role of indirect taxes for the state budget of Ukraine is determined. Thus, the fiscal significance of indirect taxes has become less due to the economic, social and political changes that have taken place in the country. To increase their fiscal potential, measures such as stimulating domestic consumption, improving the system of control over the circulation of goods, strengthening customs control and effective implementation of anti-crisis measures can be considered. The regulatory function of indirect taxes is of primary importance in terms of its impact on the national economy. Tax regulation is a set of measures aimed at government intervention in the market economy in accordance with the concept of development. The fiscal potential of indirect taxes depends on several factors, such as the state of the economy, employment, income, and others. The greater the economic activity and spending of the population, the greater the opportunity for the state to collect revenue from indirect taxes. Indirect taxes are an effective tool for managing the economy and ensuring sustainable development of the country. However, to improve the efficiency of their use and increase revenues from indirect taxes, it is necessary to constantly improve the taxation system, direct revenues to the development of social infrastructure and support for business activities. The analysis of the fiscal and regulatory role of indirect taxes in Ukraine shows that these taxes play an important role in generating budget revenues and regulating economic processes in the country.